KRITIK IBN TAIMIYAH TERHADAP PAHAM WAHDATUL WUJUD - Hairul Hudaya (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
In general, sufisrn consist of threc kinds, arc salaf"i's sullsnr, surrni's sufism, and falsafi's sufism. Salafi's sufism is a sufism whiclt its teaching and methods put under Qur'an dan the prophet tradition. The plophet traclitiott and spiritual practiccs of salaf gcncration. Sunni's Sul'isrn is a Sufisnr which ils teaching tries to combins bctwccn syari'ah and rcality, but addcd by nov interpretation and mcthod not klgwn in salaf al-shdlih periocl. Whilc thc falsafi's Sufism is a Sufism which its teaching tries to cornhinc Sufisnr and philosophy vision that beyond the syari'ah limits. In the course of timc, falsafi's Sufism were divided in big thrce schools, are hulul, ittihad and wahdqtul wujrtd which they have the similar god's orientation, that unity ol' man and god. For the supporters of wahdat al-wujtt./, this kind of teaching is the ultimate tauhid that united the absolute reality of being and refused the others one. While the contrary pcoplc argucd that thc oncncss (thc absolutc bcing) was only irt character ol'God and not {br the all bcing. Latter, this sulisrn tcaching gol. the critics and fulmination from many muslim people lbr its pre ferencc to make the same between the creature and god. Among the people who criticizcd strongly to thought of the unity of god and creature was lbn Taimiyah. Accoring to him, the thought that the being of god is the same witlr thc being ol'creaturc is clearly infidel. This writing try to study the critic ol' Ibn Taimiyah toward concept of wuhdatul wujud and its likewise with the argumentation of his critic.